Analisis Metode Rekrutmen dan Seleksi dalam Meningkatkan Kinerja Pegawai di Koperasi Credit Union Sauan Sibarrung - Silambi, Christovorus Aldino; Pasae, Yoel; Baharuddin, Baharuddin (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
The issue of educational access inequality in remote areas remains a pressing challenge in achieving equitable development, particularly in developing countries. This study examines the root causes, implications, and potential solutions to educational access disparities in remote regions through a qualitative approach, utilizing literature review and library research methods. The research highlights the multifaceted nature of this gap, which is influenced by geographical barriers, inadequate infrastructure, limited teacher availability, and socioeconomic factors. Furthermore, the analysis underscores the interplay between ineffective policy implementation and insufficient funding allocations as key contributors to the persistent challenges. By synthesizing findings from relevant academic works, governmental reports, and international case studies, this article identifies promising alternative solutions, such as community-based education initiatives, digital learning platforms, and public-private partnerships. These approaches have demonstrated success in bridging educational gaps in other contexts and hold potential for adaptation in remote areas. The study concludes by proposing a comprehensive policy framework emphasizing inclusive and sustainable solutions tailored to local needs. It calls for greater collaboration among policymakers, educational institutions, and local communities to foster equitable access to quality education. This research contributes to the discourse on education equity by offering actionable insights and alternative strategies for mitigating access disparities, ultimately supporting efforts to achieve Sustainable Development Goal 4: Quality Education for All.